2017
DOI: 10.1038/s41467-017-02101-2
|View full text |Cite
|
Sign up to set email alerts
|

Glutaminolysis drives membrane trafficking to promote invasiveness of breast cancer cells

Abstract: The role of glutaminolysis in providing metabolites to support tumour growth is well-established, but the involvement of glutamine metabolism in invasive processes is yet to be elucidated. Here we show that normal mammary epithelial cells consume glutamine, but do not secrete glutamate. Indeed, low levels of extracellular glutamate are necessary to maintain epithelial homoeostasis, and provision of glutamate drives disruption of epithelial morphology and promotes key characteristics of the invasive phenotype s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 40 publications
(56 reference statements)
1
67
0
Order By: Relevance
“…More importantly, this signaling contributes to the invasive ability and metastasis confirmed by Transwell assay and mice model. These results are in line with the discovery that glutamate secretion contributes to the aggressive behaviors of TNBC cells 40 and knockout of GPER significantly reduced lung metastases in transgenic mice model of mammary tumorigenesis. 44 The aggressiveness of TNBC cells causally leads to high incidence rates of metastasis and poor prognosis in patients with TNBC.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…More importantly, this signaling contributes to the invasive ability and metastasis confirmed by Transwell assay and mice model. These results are in line with the discovery that glutamate secretion contributes to the aggressive behaviors of TNBC cells 40 and knockout of GPER significantly reduced lung metastases in transgenic mice model of mammary tumorigenesis. 44 The aggressiveness of TNBC cells causally leads to high incidence rates of metastasis and poor prognosis in patients with TNBC.…”
Section: Discussionsupporting
confidence: 86%
“…39 a abcd e revealed that normal mammary epithelial cells do not secrete glutamate, while invasive breast cancer cells release glutamate, which contributes to the intrinsic aggressiveness of these cells. 40 The secretion of glutamate induces HIF1α in TNBC cells that contributes to aggressive behaviors. 24 The antitumor activity of the glutaminase inhibitor, which decreases glutamate concentration, is dependent on extracellular glutamate in TNBC in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In 1978, Lawrence et al observed that glutamine is the major energy source in HeLa cell line (158). Additionally, evidence supports that glutaminolysis provides metabolites, such as glutamate to promote tumor growth, as observed by Dornier et al (159). The group investigated the participation of glutamine metabolism in invasive processes so that, they showed that mammary epithelial cells from normal tissue uptake glutamine, yet glutamate secretion was not observed.…”
Section: Glutaminolysis and Mtorc1 In Cancermentioning
confidence: 71%
“…Thus, glutamine can undergo glutaminolysis by glutamine synthetase to yield glutamate, which can be further deaminated into a-ketoglutarate and enter the TCA cycle. Glutamine and glutamate metabolism correlates with the expression of EMT-associated transcription factors (37) and glutaminolysis may serve as a driver of invasiveness of breast cancer cells (38). To analyze the contribution of glutamine to the aggressive behavior of 537S-ER-expressing cells, MCF-7 cells expressing either 537S-ER or WT-ER, were grown in the presence of E2 under glucose deprivation conditions (described under "Material and Methods").…”
Section: Glutamine Supports Aggressive Behavior Of Mutated-erexpressimentioning
confidence: 99%